St Andrews Journal of International and Language Education Forum: Our Voices - Stringer, Thomas; Hopkyns, Sarah; Chong, Sin-Wang; Ngo, Xuan Minh; Jordan, Eoin (St Andrews Journal of International and Language Education, 2025)
This editorial forum piece celebrates the inauguration of the St Andrews Journal of International and Language Education (SAJILE), an open access online journal hosted by the International Education and Lifelong Learning Institute (IELLI), University of St Andrews, co-run by students and academic staff. Five key figures in the genesis of SAJILE explore their hopes for the journal, and celebrate its supportive, inclusive, and developmental mission of promoting research for, of, and as teaching by teachers, teacher educators, and early career researchers.